The needs analysis of biology handout development on the human circulatory system topic - Farida Rahmi; Badruzsaufari Badruzsaufari; Suyidno Suyidno (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
The availability of teaching materials greatly supports the quality of learning and helps students understand the subject matter. A teacher needs to convey material based on students' characteristics and the applicable curriculum to achieve an effective and efficient learning process. This study aims to analyze the need to develop biology handouts on human circulatory system material. The data collection instrument is using an online questionnaire. The research data were analyzed descriptively. The subjects of this study consisted of a biology teacher and 123 students of class XII MIA. The results showed the analysis of students' needs for the development of biology teaching materials on the concept of the human circulatory system with a percentage of 69.9%. Teaching materials significantly impact the ease of learning biology, and handouts are essential at these research locations. Similar research also needs to be carried out at various levels of education and on different materials.Abstrak Ketersediaan bahan ajar sangat mendukung kualitas pembelajaran dan membantu peserta didik memahami materi pelajaran. Seorang guru perlu menyampaikan materi yang sesuai dengan karakteristik peserta didik dan kurikulum yang berlaku untuk mencapai proses pembelajaran secara efektif dan efisien. Penelitian ini bertujuan untuk menganalisis perlunya pengembangan handout biologi pada materi sistem peredaran darah manusia. Instrumen pengumpulan data yaitu menggunakan kuisioner secara online. Data penelitian dianalisis secara deskriptif. Subyek penelitian ini terdiri dari seorang guru biologi dan 123 peserta didik kelas XII MIA. Hasil penelitian menunjukkan bahwa analisis kebutuhan peserta didik terhadap pengembangan bahan ajar biologi pada konsep sistem peredaran darah manusia dengan persentase 69,9%. Bahan ajar berdampak signifikan terhadap kemudahan belajar biologi, dan handout penting di lokasi penelitian ini. Penelitian serupa juga perlu dilakukan pada berbagai jenjang pendidikan dan pada materi yang berbeda.